Memory, literature and law: the witness representation in literature about human rights violations in Chile (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This article reviews how the witness figure has been used in two chilean novels that have been recently published: La dimensión desconocida, from Nona Fernández and Monte Maravilla, from Miguel Lafferte. Both script plots are based in real cases, places and historical characters  (although treated as fiction), related to Pinochet´s dictatorship. They present a complex and intrincate witness figure, through the form a regretful torturer, a girl who will be the future´s narrator or a ghost that happens to be real. Meanwhile, in light of the witness understood as an common articulating figure for the law, as well as for literature, the article wants to reflect on judicial processes posibilities, while narrative, as colective memory sources that can be held accountable for the horror. The witness role turns out to be essential in both discourse  fields: meanwhile in judicial procesess the witness is the subject of the testimony enunciation and, as such, an evidence element for criminal liabilities determination, in literature, the witness has important narrative as well as ethics implications, wich give such richness to the testimony, that it becomes an effective way of memory that not only narrates what happened, it closes to show it.
Keywords: Memory; law; novel; post dictatorship novel; witness